Pengaruh Laju Eksploitasi Terhadap Keragaan Reproduktif Ikan Tembang (Sardinella gibbosa) di Perairan Pesisir Jawa Barat - Ernawati, Yunizar; Kamal, Mohammad Mukhlis (JURNAL BIOLOGI INDONESIA, 2010)
ABSTRACTEffect of Exploitation Rate on Reproductive Performance in Goldstripe Sardinella (Sardinellagibbosa) in West Java Coastal Waters. The research objective was to explore the effect ofexploitation rate on reproductive performance of goldstripe sardinella (Sardinella gibbosa).Three sites located in West Java coasts were selected representing coastal areas adjacent tothe Indian Ocean (Palabuhan Ratu), Java Sea (Blanakan), and Sunda Strait (Labuan), for fishcollection during May-July 2009. Fish samples were collected and the length was measuredprior to sex determination, observation on gonad morphology as well as gonad maturitydetermination, examination on fecundity and eggs diameter, and protein content analysis.Estimation on exploitation rate (E) was calculated based on length data performance fromwhich the result was correlated with reproductive parameters including the length at firstmaturity, fecundity, eggs distribution and diameter, and protein content analysis. By sitesbasis, variation in E was consistently shown only by eggs protein content in which the lowerthe E estimation the higher the protein contents. However, in response to E, there wereinconsistencies shown by the length at first maturity, fecundity, and eggs diameter. Suchinconsistencies are thought to be associated with population structure of matured female, andvariability in the habitat conditions which determines the magnitude of fish stock.Key words: Sardinella gibbosa, exploitation rate, reproductive performance